NBP35 encodes an essential and evolutionary conserved protein in Saccharomyces cerevisiae with homology to a superfamily of bacterial ATPases - Vitale, Gaetano; Fabre, Emmanuelle; Hurt, Ed (Gene, 1996)
We have cloned a novel and essential gene, NBP35, from Saccharomyces cerevisiae that encodes a putative Nucleotide Binding Protein of 35 kDa. Sequence analysis revealed structural homology of Nbp35p with a family of bacterial ATPases involved in cell division processes and chromosome partitioning. A search in databases identified closely related sequences from yeast and higher eukaryotes, suggesting a conserved function for this family of proteins. By indirect immunofluorescence, a tagged version of Nbp35p carrying two immunoglobulin G-binding domains derived from Staphylococcus aureus Protein A was localised to the nucleus. A single amino-acid substitution in the conserved nucleotide-binding motif of Nbp35p renders the protein non-functional. Furthermore, a conserved cluster of four cysteines in the N-terminal end of the protein is also required for an essential role of Nbp35p.